Modern Methods of Bile Acid Analysis by Mass Spectrometry: A View into the Metabolome - William Griffiths (Current Analytical Chemistry, 2007)
The advent of the “omics” revolution has reawakened an interest in the mass spectrometric analysis of bile acids, particularly in the related fields of lipidomics and metabolomics. This is due to the presence of bile acids in body fluids and their potential to act as biomarkers. Bile acids and bile alcohols are formed from cholesterol in the liver. Bile acids are excreted from the liver into the small intestine via the bile duct conjugated with glycine or taurine at the side-chain carboxyl group. After assisting in the lipolysis and absorption of fats in the intestinal lumen, bile acids are returned to the liver. Bile acids and bile alcohols undergo further metabolism by bacterial and hepatic enzymes during the enterohepatic circulation, including hydrolysis of conjugates, oxidation and reduction, isomerisation, dehydroxylation and hydroxylation. The hydroxyl groups may also be conjugated with sulphuric acid, glucuronic acid, glucose or N-acetylglucosamine in the liver and in extrachepatic organs including intestine and kidney. Thus, the mixture of metabolic products of cholesterol in biological fluids can be very complex. Here we describe modern mass spectrometric methods used to characterise this diverse range of molecules found in biological fluids.